Identifikasi Keselamatan Dan Kesehatan Kerja Menggunakan Metode Hazop Dan Bowtie Pada PT Alis Jaya Ciptatama - Thegar Gilang Rachmawan; Widya Setiafindari (Jurnal Kendali Teknik dan Sains, 2023)
The purpose of this study is to find out what are the most dominant work accidents, what are the impacts that occur from work accidents, as well as appropriate risk control adventures for work accidents due to 13 work accidents in 2021 to 2023 which cause a loss of 33 working hours day at PT Alis Jaya Ciptatama. The method used is the Hazard And Operability Study (HAZOP) method and Bowtie analysis to identify potential occupational safety and health hazards by limiting the probability criteria in quantitative and consequence calculations and analyzing the risk path from cause to consequence using a bowtie diagram. The results obtained are that the highest activity is in activity code 3b with an LI value of 38.3, then in the smallest activity code 2a with an LI value of 10. The risks that occur fall into the high, medium, and low severity categories, so the warning given What is given is to install machine guards and ensure the operator has qualified machine usage skills.